First record of a Dung Midge within the South Atlantic island group of Tristan da Cunha (Diptera: Scatopsidae). - Hänel, Christine; Haenni, Jean-Paul (Contributions to Entomology = Beiträge zur Entomologie, 2007)
Scatopsidae Dung Midges have not been known to occur within the south Atlantic island group of Tristan da Cunha. The finding in 2005 of Scatopse notata (Linnaeus, 1758) at Nightingale Island marks the occurrence of a member from that family at the archipelago for the first time. As such, it also documents the species presence in the Afrotropical region for which no previous records are known. Here we report on the finding of S. notata at Nightingale Island, and put forward the scenarios under which its arrival may have occurred. Keywords Diptera, Scatopsidae, Scatopse, Dung Midge, fly, Tristan da Cunha, Nightingale Island, South Atlantic, introduction.